1998
DOI: 10.1046/j.1464-410x.1998.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium and calcium chelator on the response of the bladder to in vitro ischaemia

Abstract: Objective To examine the eCect of diCerent concensolution, resulted in a diminished response to all stimuli. This contractile dysfunction was least in the trations of calcium on the contractile responses of isolated strips of rabbit bladder detrusor to various presence of calcium chelator (EGTA) and greatest in the presence of 5.4 mmol/L calcium. Repetitive stimuforms of stimulation after 2 h incubation in the presence of substrate and oxygen depletion (in vitro ischaelation during in vitro ischaemia also exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 27 publications
4
24
0
Order By: Relevance
“…This is consistent with previous studies showing that neuronal membranes (responsible for neurotransmitter release by FS) are significantly more sensitive to hypoxic and I/R damage than muscarinic receptors (which are stimulated by carbachol) or smooth muscle cell membranes (which are depolarized by KCl) [5,6,12,[13][14][15] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with previous studies showing that neuronal membranes (responsible for neurotransmitter release by FS) are significantly more sensitive to hypoxic and I/R damage than muscarinic receptors (which are stimulated by carbachol) or smooth muscle cell membranes (which are depolarized by KCl) [5,6,12,[13][14][15] .…”
Section: Discussionsupporting
confidence: 93%
“…Studies using an in vitro model of I/R have clearly demonstrated that this model produces contractile and metabolic damage similar to that of partial outlet obstruction [5,6] . The metabolic damage is mediated by the oxidation of proteins and lipids within the various cellular and subcellular membrane systems and can be quan-titated by analyzing the affected tissue for the oxidative metabolite malondialdehyde (MDA) [5,6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, the detrusor dysfunction is caused by activation of specific hydrolytic enzymes including calpain and phospholipase A 2 with subsequent damage to intracellular organelles such as the mitochondria and sarcoplasmic reticulum and via generation of reactive oxygen species and subsequent membrane lipid peroxidation (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Levin et al demonstrated that, when muscle tissue was exposed to free radical generation, there was an accumulation of calcium in the intracellular medium, which would be responsible for cell damage. Thus, they suggested that galangin would act through type L calcium channels, thereby avoiding increased transportation of calcium ions into cells (17). There would, of course, be a need for studies to elucidate the exact mechanism for the action of galangin, in order to characterize the diseases for which galangin could become part of the therapeutic arsenal.…”
Section: Discussionmentioning
confidence: 99%